2022
DOI: 10.3389/fphys.2022.913673
|View full text |Cite
|
Sign up to set email alerts
|

Age-Associated Dysregulation of Integrin Function in Vascular Smooth Muscle

Abstract: Arterial aging results in a progressive reduction in elasticity of the vessel wall and an impaired ability of aged blood vessels to control local blood flow and pressure. Recently, a new concept has emerged that the stiffness and decreased contractility of vascular smooth muscle (VSM) cells are important contributors to age-induced arterial dysfunction. This study investigated the hypothesis that aging alters integrin function in a matrix stiffness-dependent manner, which contributes to decreased VSM contracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…The observed decrease in complexity of the microvascular network might be a consequence of progressive damage of elastin and increased stiffness of the extracellular matrix (ECM) in large conduit vessels, a process associated with vascular aging in mammals (Avolio et al 1998 Increased vascular stiffness is also the result of an increased collagen/elastin ratio, calci cation of the remaining elastin, phenotypic switching of smooth muscle cells (SMC) from the contractile to proliferative phenotype, and endothelial dysfunction (Duca et al 2016;Mochizuki et al 2002). Increased stiffness of the ECM causes altered anchoring of SMCs to ECM through integrin β1 and modulation of SMC α-actin cytoskeleton, resulting in their decreased ability to sense mechanical changes in the environment and decreased SMC contractility (Ojha et al 2022). Decrease in aorta elasticity results in the loss of the Windkessel effect and increased pulse pressure without change in the mean arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…The observed decrease in complexity of the microvascular network might be a consequence of progressive damage of elastin and increased stiffness of the extracellular matrix (ECM) in large conduit vessels, a process associated with vascular aging in mammals (Avolio et al 1998 Increased vascular stiffness is also the result of an increased collagen/elastin ratio, calci cation of the remaining elastin, phenotypic switching of smooth muscle cells (SMC) from the contractile to proliferative phenotype, and endothelial dysfunction (Duca et al 2016;Mochizuki et al 2002). Increased stiffness of the ECM causes altered anchoring of SMCs to ECM through integrin β1 and modulation of SMC α-actin cytoskeleton, resulting in their decreased ability to sense mechanical changes in the environment and decreased SMC contractility (Ojha et al 2022). Decrease in aorta elasticity results in the loss of the Windkessel effect and increased pulse pressure without change in the mean arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…3C). This may be related to the time at which risk factors affecting the vasculature (e.g., hyperlipidemia, hypertension) play a role in the vascular branches supplying the brainstem [10]. Moreover, the older the age, the longer the risk factors remain [11][12][13], and the greater the chance of causing brainstem cavernous hemangioma.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that NDR2 controls substrate selectivity by regulating integrin subunit availability in growth cones during neurite growth (Demiray et al, 2018 ). Notably, integrin receptor regulation is also addressed in aging-associated pathologies, as enhancing integrin signaling holds promise in alleviating impairments in blood-brain barrier integrity in rats (Halder et al, 2023 ) and promoting cellular regeneration (Rozo et al, 2016 ; Ojha et al, 2022 ).…”
Section: Altered Intracellular Communicationmentioning
confidence: 99%